The Arizona Prevention Research Center partnerships in Arizona to promote COVID-19 vaccine health equity - Tomas Nuño; Tomas Nuño; Lidia Azurdia Sierra; Ada Wilkinson-Lee; Scott Carvajal; Jill de Zapien; Kiera Coulter; Carlos Figueroa; Mario Morales; Ramses Sepulveda; Refugio Sepulveda; Maia Ingram (Frontiers Media S.A., 2022)
BackgroundVaccine hesitancy in the face of the COVID-19 pandemic is a complex issue that undermines our national ability to reduce the burden of the disease and control the pandemic. The COVID-19 pandemic revealed widening health disparities and disproportionate adverse health outcomes in terms of transmission, hospitalizations, morbidity and mortality among Arizona's Latinx rural, underserved, farmworker, disabled and elderly populations. In March 2021, ~8.1% of those vaccinated were Latinx, though Latinxs make up 32% of Arizona's population. The Arizona Vaccine Confidence Network (AzVCN) proposed to leverage the expertise of the Arizona Prevention Research Center (AzPRC) and the resources of the Mel and Enid Zuckerman College of Public Health (MEZCOPH) Mobile Health Unit (MHU) to identify, implement and evaluate a MHU intervention to increase uptake of COVID-19 vaccines.MethodsThe AzVCN focused efforts on Latinx, rural, un/underinsured and farmworker communities in the four Arizona border counties that are at greater risk of COVID-19 morbidity and mortality and may have limited access to vaccination and other essential health services. The AzVCN used listening sessions to create a feedback loop with key stakeholders and critical health care workers to validate barriers/enablers and identify solutions to increase vaccination uptake emerging from the network. The AzVCN also implemented a community-based intervention using community health workers (CHWs) based in a MHU to increase knowledge of the COVID-19 vaccines, reduce vaccination hesitancy and increase vaccination uptake among Latinx rural, un/underinsured and farmworker populations in Southern Arizona.ResultsAzVCN outcomes include: identification of enablers and barriers of COVID-19 vaccination in the priority populations; identification of strategies and solutions to address vaccine hesitancy and increase vaccine uptake among priority population; and evidence that the proposed solutions being tested through the AzVCN contribute to increased vaccine uptake among the priority populations.ConclusionThrough these efforts the AzPRC contributed to the CDC's Vaccinate with Confidence Strategy by collaborating with CHWs and other key stakeholders to engage directly with communities in identifying and addressing structural and misinformation barriers to vaccine uptake.